Real-world outcomes of third-line immune checkpoint inhibitors versus irinotecan-based chemotherapy in patients with advanced gastric cancer: a Korean, multicenter study (KCSG ST22-06) - Sung Hee Lim; Keun-Wook Lee; Jae-Joon Kim; Hyeon-Su Im; In-Ho Kim; Hye Sook Han; Dong-Hoe Koo; Jang Ho Cho; Chi Hoon Maeng; Min-Young Lee; Hyo Jin Lee; Jwa Hoon Kim; et al. (BMC Cancer, 2024)
Abstract Background Immune checkpoint inhibitor (ICI) or irinotecan-based chemotherapy is frequently used after failure of second-line paclitaxel plus ramucirumab treatment for patients with locally advanced unresectable or metastatic advanced gastric cancer (AGC). This study aimed to compare the efficacy between ICI and irinotecan-based chemotherapy as third-line treatment in patients with AGC. Methods We retrospectively reviewed patients with AGC, whose third-line treatment started between July 2019 and June 2021 at 17 institutions in Korea. The ICI group included patients who received nivolumab or pembrolizumab, and the irinotecan-based chemotherapy group included patients who received irinotecan or FOLFIRI (5-fluorouracil, leucovorin and irinotecan). Results A total of 363 patients [n = 129 (ICI) and n = 234 (irinotecan-based chemotherapy)] were analyzed. The median progression-free survival was 2.3 and 2.9 months in ICI and irinotecan-based chemotherapy groups, respectively (p = 0.802). The median overall survival (OS) was 5.5 and 6.0 months in ICI and irinotecan-based chemotherapy groups, respectively (p = 0.786). For all patients included in this study, multivariable analysis showed that weight loss, peritoneal metastasis, low serum sodium or albumin, and short duration of second-line treatment were associated with inferior OS (p < 0.05). ICI showed significantly longer OS than irinotecan-based chemotherapy in patients without peritoneal metastasis. Whereas ICI showed significantly shorter OS in patients without PD-L1 expression than irinotecan-based chemotherapy. Conclusions No significant difference in survival outcome was observed between ICI and irinotecan-based chemotherapy as third-line treatment for AGC patients. ICI might be preferred for patients without peritoneal metastasis and irinotecan-based chemotherapy for patients with tumors without PD-L1 expression. Trial registration This study was registered in the Clinical Trial Registry of Korea ( https://cris.nih.go.kr : KCT 0007732).